Analysis of respiratory tract infections in intensive care unit of a hospital in southern Brazil (Research, Society and Development, 2021)
Hospital infections increase morbidity and mortality and cause financial losses for health institutions, and the risk is higher in intensive care units, due to patients’ frailty, the use of large spectrum antibiotics and frequent invasive procedures. In this regard, respiratory tract is the most affected and its main risk factor is the mechanical ventilation. This study aims to determine prevalence and characteristics of respiratory infections that occur in patients hospitalized in these units. This is a retrospective study, based on notifications of hospital infection, from January 2017 to December 2019, which occurred in intensive care units of a tertiary hospital in Paraná. There was a total of 398 notifications, while the respiratory tract was responsible for 68.3% of the cases. Ventilator-associated pneumonias were the most prevalent. Nevertheless, it showed a decline in the period studied. Tracheobronchitis, although less prevalent, had the highest lethality rate (31.6%). Methicillin-resistant Staphylococcus aureus was the most frequent microorganism (11%), followed by Pseudomonas aeruginosa (9.6%). Yet, the most used therapeutic regimen for these infections’ treatment was piperacillin-tazobactam (43%). This study contributed with epidemiological data of nosocomial infections from the researched institution, making it possible to elect strategics and prevention measures with greater specificity and targeting the local reality. In addition, it can be useful in comparations with future studies.